The resilient farm and homestead : 20 years of permaculture and whole systems design - Falk, Ben, 1977- (Chelsea Green Publishing, 2024)
"A definitive twenty-first century permaculture manual for human flourishing in an age of disconnection, disease, and decline. Drawing from twenty years of experience as a land designer and site developer, in The Resilient Farm and Homestead, Revised and Expanded Edition author Ben Falk describes how he has transformed a degraded hillside in the frigid climate of Vermont into a thriving Garden of Eden that now provides year-around abundance and regeneration for his family and community. First published in 2013, The Resilient Farm and Homestead is a comprehensive how-to guide for building durable and productive land-based systems through the reciprocal interplay of humans and the natural world. In the ten years since he first published this seminal work, Falk has only deepened his wisdom in harnessing nature-based solutions for an increasingly perilous planet. Coming on the heels of the unprecedented upheaval of Covid-19, this new and expanded edition of The Resilient Farm and Homestead couldn't be more timely. More than just a collection of tricks and techniques for regenerative site development, the book covers nearly every strategy Falk and his team have tested at the Whole Systems Research Farm over the past two decades. The book includes detailed information on earthworks, gravity-fed water systems, soil fertility management, growing nutrient-dense food and medicine, fuelwood production and processing, agroforestry, managed grazing, and much more. The book presents a viable home-scale model for an intentional food-producing ecosystem in cold climates and beyond. Inspiring to would-be homesteaders everywhere, Falk is an inspiration for what can be done by working with and guiding natural systems and making the most of what we have by reimagining what's possible. Complete with full-color photography and detailed design drawings, The Resilient Farm and Homestead, Revised and Expanded Edition includes new information on: -Designing greenhouses and microclimates -Zone 4 permaculture -Reinvigorating human health -Raising children on a homestead -Top-performing plants -The power of woodchips -Efficient and resilient energy systems -Beekeeping -And much, much more! "Essential reading for the serious prepper as well as for everyone interested in creating a more resilient lifestyle."-Carol Deppe, author of The Resilient Gardener "This intelligent, challenging book, rooted somewhere between back-to-the-land idealism and radical survivalism, sees resilience as both planting and building for the use of future generations, but also as preparing food, water, shelter, and the human body and psyche for the onset of any imaginable extreme emergency. . . . The result is a comprehensive, open-ended, theoretical and practical system for a post-carbon-dependent life."-Publishers Weekly (starred review of first edition)"--